2021
DOI: 10.3390/fib9030017
|View full text |Cite
|
Sign up to set email alerts
|

Online Pre-Treatment of Thermomechanical Pulp with Emulsified Maleated Polypropylene for Processing of Extruded Thermoplastic Composites

Abstract: The effectiveness of maleated polypropylene (MAPP) in emulsified form for the pre-treatment of thermo-mechanical pulp (TMP) before extrusion with polypropylene fibres was evaluated. MAPP in pellet form, which was applied during the compounding step, served as a benchmark. In addition, commercial softwood flour was included as a reference. The influence of the temperature during the defibration process and the presence or absence of the coupling agent on composite performance were evaluated. Composites were pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…However, it could be observed that the pulp loading percentage has a significant influence on the physical and mechanical properties of the WPCs. WPCs highly filled with wood fibre and pulp have obvious advantages in terms of their environmental friendliness, application scenarios, and market competitiveness, and they are continuously being developed [ 40 , 41 ]. Most published papers have reported 60% as the maximum loading percentage of filler to produce WPCs with good properties [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, it could be observed that the pulp loading percentage has a significant influence on the physical and mechanical properties of the WPCs. WPCs highly filled with wood fibre and pulp have obvious advantages in terms of their environmental friendliness, application scenarios, and market competitiveness, and they are continuously being developed [ 40 , 41 ]. Most published papers have reported 60% as the maximum loading percentage of filler to produce WPCs with good properties [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…MAPP is usually added to the matrix, but can also be added to the fibers; 25 it increases the compatibility between fiber and matrix through hydrogen bonding or esterification between the maleic anhydride and the hydroxyl groups on the fibers 26,27 . Compared to nonlignin containing fibers, 25,27–29 MAPP is less effective as a compatibilizer between TMP and PP. This is due to the presence of lignin on the TMP surface.…”
Section: Introductionmentioning
confidence: 99%
“…Maleic anhydride grafted polypropylene (MAPP) is a common compatibilizer used for wood-thermoplastic composites. MAPP is usually added to the matrix, but can also be added to the fibers; 25 it increases the compatibility between fiber and matrix through hydrogen bonding or esterification between the maleic anhydride and the hydroxyl groups on the fibers. 26,27 Compared to nonlignin containing fibers, 25,[27][28][29] MAPP is less effective as a compatibilizer between TMP and PP.…”
Section: Introductionmentioning
confidence: 99%